Caffeine metabolites are associated with different forms of caffeine supplementation and with perceived exertion during endurance exercise - Whalley, Peter; Paton, Carl; G. Dearing, Chey (Biology of Sport, 2021)
This investigation compared the urine caffeine metabolites produced from different forms of caffeine supplementation given to runners 15 minutes before a series of 5-km running trials. Fourteen amateur competitive runners completed a series of self-paced outdoor time trials following ingestion of placebo or one of three alternate forms of caffeine supplement. Trials were randomized in a crossover design with equivalent doses of caffeine (4.0 mg.kg-1) administered 15 minutes before each trial via chewing gum, a novel dissolvable mouth strip or tablet. Runners produced a urine sample following each caffeinated trial that was tested for caffeine and its metabolites by high-performance liquid chromatography. The tablet form of caffeine produced a lower (p = 0.04) urinary ratio of the metabolite paraxanthine to caffeine compared with either gum or strip. Independently of caffeine delivery mode, subjects who metabolized a higher proportion of caffeine to paraxanthine recorded a lower (p = 0.01) perceived exertion. We demonstrate that oral swallowed caffeine administered 15 minutes before 5-km running is less metabolized compared with caffeinated products designed to be chewed or dissolved in the mouth. We suggest the metabolism of caffeine to paraxanthine has an inverse relationship with perceived exertion independently of caffeine delivery mode.